A dynamic PDE solver for breasts cancerous cell visualization on distributed parallel computing systems - Alias, Norma; Islam, Md. Rajibul; Rosly, Nur Syazana (2009)
Since distributed parallel computing system offers users with more spread computing and storage resources, it provides us a prospect to propose new efficient and dynamic solvers for the numerical solutions of partial differential equations (PDEs) in order to visualize breasts’ cancerous cell. Partial differential equations (PDEs) can be classified as parabolic equation, elliptic equation and hyperbolic equation. Partial differential equations are used commonly as mathematical models for solving all of the science and engineering fields. This research will focus on the study of elliptic equations, particularly Helmholtz’s wave equation and hyperbolic equations. The numerical finite-difference method is chosen as a platform for discretizating the elliptic equations and to solve the hyperbolic equations. The elliptic equation can be used as mathematical models for biological aspects of electromagnetic wave. Breast cancer is the commonest female malignancy in Malaysia as well as all over the world. The incidence of breast cancer in Malaysia is estimated to be around 27 per 100,000 populations, with close to 3,000 new cases annually. Parallel Virtual Machine (PVM) is emphasized as communication open source software on distributed parallel computing system, which results in a performance gain. The parallel performance measurements of the parallel computing is analysed in this study.